2019
DOI: 10.1055/a-0999-5282
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of probe-based confocal laser endomicroscopy in superficial non-ampullary duodenal epithelial tumors

Abstract: Background and study aims  Endoscopic diagnosis of superficial non-ampullary duodenal epithelial tumors (SNADETs) has not been established. Probe-based confocal laser endomicroscopy (pCLE: Cellvizio) provides real-time endomicroscopic analysis. We developed and validated a new pCLE classification of SNADET based on abnormal findings. Patients and methods  pCLE scanning of 20 SNADET lesions including 16 adenomas and four carcinomas was retrospectively evaluated to explore abnormal pCLE findings in relation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Likewise, Tahara et al . [ 52 ] indicated that the dark epithelium and distorted crypt structure are characteristic pCLE features of neoplasia and cancer in SNADETs, with a sensitivity and specificity of nearly 100%. In terms of ECS, Hirose et al .…”
Section: Endoscopic Diagnosis For Snadetsmentioning
confidence: 99%
“…Likewise, Tahara et al . [ 52 ] indicated that the dark epithelium and distorted crypt structure are characteristic pCLE features of neoplasia and cancer in SNADETs, with a sensitivity and specificity of nearly 100%. In terms of ECS, Hirose et al .…”
Section: Endoscopic Diagnosis For Snadetsmentioning
confidence: 99%
“…In addition, we dissected an apron flap for total laryngectomy in 11 patients (84.6%; No. [3][4][5][6][7][8][9][10][11][12][13]. Microvascular defect reconstruction was necessary in 7 patients (53.8%).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Non-invasive methods to characterise mucosal changes of the head and neck region, such as narrow-band imaging, confocal laser imaging, optical coherence tomography and fluorescence endoscopy, have been emerging recently [1][2][3][4] . One method that has shown a potential advance regarding its broad application outside of experimental studies is confocal laser endomicroscopy (CLE), which has demonstrated its value in the fairly similar oesophageal, gastric and intestinal epithelium in a wide range of clinical applications [5][6][7][8] . CLE is usually performed with the systemic application of fluorescein, which stains the intercellular spaces and allows realtime, non-invasive examination of the surface epithelium, cell features and fine capillary system to resemble a histological examination in detail and resolution 9 .…”
Section: Introductionmentioning
confidence: 99%